Economic Analysis of Large-Scale Pumped Storage Plants in Norway. (January 2016) - Henden, Arild Lote; Doorman, Gerard; Helseth, Arild
Abstract: The European power system needs to develop mechanisms to compensate for the reduced predictability and high variability that occur when integrating renewable energy. Construction of pumped storage plant (PSP) is a solution. In this article an economic analysis of large-scale PSP in Norway is made considering sales of energy. The analysis is carried out with a power market model and a 2030 projection of the Northern Europe power system. The effect of varying the PSP capacity and transmission capacity between Norway and Europe is studied. A substantial increase in transmission capacity from Norway to Europe is needed for PSP to be profitable for the owners and the Scandinavian socio-economic surplus. 14100 MW transmission capacities and 950 MW new PSP capacity give the highest socio-economic surplus in this analyse, which increase by 800 M€/year compared with expected 2030 capacity on transmission and PSP.